Ultrasound-Guided Paravertebral Regional Anesthesia in Water Buffalo - Shokry, Mohammed Mostafa (Journal of Buffalo Science, 2012)
Adequate flank regional anaesthesia was achieved using ultrasound-guided nerve block of the 13th thoracic, 1st and 2nd lumbar spinal nerves after their exits from their intervertebral foraminae with only 5 ml of lidocaine 2%. Twelve successful trials were conducted on 4 buffaloes without any complications.